2012
DOI: 10.1007/s00167-012-2221-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind clinical trial of tourniquet application strategies for total knee arthroplasty

Abstract: Inflation of an automatic pneumatic lower limb tourniquet before skin incision and its deflation after hardening of cement tends to give better outcomes in TKA patients during six postoperative days. The estimated blood loss was highest when the tourniquet was inflated just before cement application and deflated after its hardening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
62
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 38 publications
1
62
2
1
Order By: Relevance
“…Blood loss in patients with a tourniquet for cementation only was a mean 1795 mL compared to our mean 574 mL. The study by Kvedaras et al [5] is well designed -preoperative medications (including alcohol) were factored into patient inclusion into the study. Results of the study showed a mean operative tourniquet time of 37 minutes versus our mean of 43 minutes.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Blood loss in patients with a tourniquet for cementation only was a mean 1795 mL compared to our mean 574 mL. The study by Kvedaras et al [5] is well designed -preoperative medications (including alcohol) were factored into patient inclusion into the study. Results of the study showed a mean operative tourniquet time of 37 minutes versus our mean of 43 minutes.…”
mentioning
confidence: 69%
“…Two studies [5,8] comparing operative tourniquet use with cementation tourniquet were published in parallel with ours. Therefore, we did not discover them with our literature search.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Although the authors mentioned that there were no previous studies comparing the effects of tourniquet used only during cementing, we found two studies on the same topic published before the current study [4,7]. Kvederas and colleagues [4] compared three groups undergoing TKA in a Level II study.…”
mentioning
confidence: 86%
“…Kvederas and colleagues [4] compared three groups undergoing TKA in a Level II study. In the first group, the tourniquet was inflated before incision and deflated after hardening of the cement.…”
mentioning
confidence: 99%